EXPERIMENTAL STUDY OF HYBRID SOLAR AIR CONDITIONING SYSTEM IN WEST SUMATERA - Kaidir Kaidir; Mulyanef -; Suryadimal -; Burmawi -; Risky Arman (Jurnal Ipteks Terapan, 2023)
Due to the near-universal presence of air conditioning systems in Indonesian buildings, the development of solar-powered air conditioning units has accelerated recently. The tropical country of Indonesia benefits from year-round sunlight. In this study, a photovoltaic (PV) system that includes a battery, a photovoltaic system composed of PV panels, a solar charger, a DC power controller/inverter, and a battery is combined with a solar-powered air conditioning system to analyze its design and performance. In locations without electricity, this air conditioning technology is usable. Obtaining approximately 1 ton of refrigeration (3.52 kW) through the first step of this research's cooling load calculation for the space to be conditioned. An estimated photovoltaic (PV) system that includes all the required connections has been constructed based on this cooling load. Temperature measurements at crucial cycle locations, including the compressor's inlet and outlet as well as the evaporator and condenser, have been made using a data logging system. All day long, measurements were made of the system's input power and coefficient of performance (COP) under Indonesia's climate. The results are compared to the performance of traditional systems and the coefficient of performance for the system ranges from 2.9 to 8.5. for the system and these results are compared with the performance of conventional systems